2014
DOI: 10.1177/0884533614554263
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complication Rates, Types, and Average Tube Patency Between Jejunostomy Tubes and Percutaneous Gastrostomy Tubes in a Regional Home Enteral Nutrition Support Program

Abstract: J-tubes are associated with higher complication rates requiring tube replacement compared with PEG tubes. The main causes of J-tube replacement are dislodgement and obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
17
0
6
Order By: Relevance
“…In a retrospective review of 560 long‐term home EN patients, Ao et al 9 compared complication rates requiring tube replacement between jejunostomy tube and PEG tube patients. The study found that, compared with PEG tubes, jejunostomy tubes are associated with higher rates of complications that require tube replacement, with dislodgement and obstruction being the main causes for tube replacement.…”
Section: Section 7 Administration: Ead Patencymentioning
confidence: 99%
“…In a retrospective review of 560 long‐term home EN patients, Ao et al 9 compared complication rates requiring tube replacement between jejunostomy tube and PEG tube patients. The study found that, compared with PEG tubes, jejunostomy tubes are associated with higher rates of complications that require tube replacement, with dislodgement and obstruction being the main causes for tube replacement.…”
Section: Section 7 Administration: Ead Patencymentioning
confidence: 99%
“…Early nutrition intervention has been shown to significantly improve outcomes, 6 8 which has caused an increase in the use of acute inpatient and long‐term home enteral nutrition (HEN) over the last few decades 9 – 13 . Despite the benefits, HEN can be associated with significant complications with the enteral tube itself (tube site infection, granulation tissue formation, leaking around insertion site, etc) or difficulties with provision of enteral formula 14 17 …”
mentioning
confidence: 99%
“…[9][10][11][12][13] Despite the benefits, HEN can be associated with significant complications with the enteral tube itself (tube site infection, granulation tissue formation, leaking around insertion site, etc) or difficulties with provision of enteral formula. [14][15][16][17] Enteral tube misconnections resulting in enteral nutrition being provided into the wrong port or tube have been increasingly reported, prompting the development of new international design standards for medical device tubing connectors. 18,19 This change is being undertaken by the Global Enteral Device Supplier Association, which has partnered with leading industry organizations, including Nestlé and Abbott Nutrition.…”
mentioning
confidence: 99%
“…A search of the hospital's protocol on PEG and jejunostomy tube returned guidelines for the role in enteral nutrition only with limited information for the care of a direct Jejunostomy for the sole purpose of medication administration. A search on CINAHL to compare rates of complications between DEJ to PEG/J retrieved only one retrospective study of 560 patients where the tubes were used for the purposes of enteral feeding indicated in patients with GIT / Head and Neck cancers, Stroke and other neurologic conditions which were not specifically identified (Ao, Sebastianski, Selvarajah, & Gramlich, 2015). Ao et al (2015) concluded that there was a higher risk of tube related complications, particularly the requirement of tube replacement in the patients with the DEJ tubes (48.4%) than that of the PEG group (21.5%).…”
Section: Peg Peg/j and Jejunostomy Tubesmentioning
confidence: 99%